“VALUES, PERUVIAN EDUCATION FUNDAMENTAL PILLARS FOR THE CREATION OF A FIRST WORLD NATION ”. - Rodriguez Del Solar, Natalia (2014)
We face a new world society :civilization of knowledge and technology, simbolic culture, free time increment, increase of scholarization, multiculturalization, and apparently, the absence of values that present a body blow to the human being in all his dimensions: afective, ethical social, esthetic and phisical. In the face of great challenges, we must improve our National Development Plan with the use of Educational Planification in order to enhance our Educational System. It engages the mother before giving birth, education of the baby, the child, the adolescent, the adult and the third age, having as the ultimate common denominator: Fundamental Values.